Regional development, income distribution and gender in Bolivia: Insights from a 2012 Social Accounting Matrix (SAM) and multiple analysis - Luis Carlos Jemio; Lykke Eg Andersen; Clemens Breisinger; Manfred Wiebelt (Institute for Advanced Development Studies (INESAD), 2015)
This paper describes the construction of the most detailed, openly accessible Social Accounting Matrix (SAM) for Bolivia to date. In addition to allowing for 'standard' socio-economic analysis common for SAMs - like assessing the linkages between production, factor income distribution and households' incomes and expenditures - the SAM presented in this paper makes detailed economic assessments at the subnational level, by gender and at detailed agricultural subsector levels, possible. Sections 1-4 present the methodology and data sources used, explain assumptions and criteria adopted for SAM disaggregation, and discuss key findings with a focus on distributional features. Section 5 presents results from a simple SAM multiplier model and section 6 concludes. It is the authors' hope that this SAM database can make a contribution to evidence-based policy making that helps to further reduce poverty and food insecurity in Bolivia.
Keywords: E16; 330; Social Accounting Matrix; Bolivia